On the Metallicities and Kinematics of the Circumgalactic Media of Damped Lyα Systems at z ∼ 2.5 - Stephanie M. Urbano Stawinski; Kate H. R. Rubin; J. Xavier Prochaska; Joseph F. Hennawi; Nicolas Tejos; Michele Fumagalli; Marc Rafelski; Evan N. Kirby; Elisabeta Lusso; Zachary Hafen (The Astrophysical Journal, 2023)
We use medium- and high-resolution spectroscopy of close pairs of quasars to analyze the circumgalactic medium (CGM) surrounding 32 damped Ly α absorption systems (DLAs). The primary quasar sightline in each pair probes an intervening DLA in the redshift range 1.6 < z _abs < 3.5, such that the secondary sightline probes absorption from Ly α and a large suite of metal-line transitions (including O i , C ii , C iv , Si ii , and Si iv ) in the DLA host galaxy’s CGM at transverse distances 24 kpc ≤ R _⊥ ≤ 284 kpc. Analysis of Ly α in the CGM sightlines shows an anticorrelation between R _⊥ and H i column density ( N _HI ) with 99.8% confidence, similar to that observed around luminous galaxies. The incidences of C ii and Si ii with N > 10 ^13 cm ^−2 within 100 kpc of DLAs are larger by 2 σ than those measured in the CGM of Lyman break galaxies (C _f ( N _C _II ) > 0.89 and ${{\rm{C}}}_{f}(N_{Si{\rm\small{II}}})={0.75}_{-0.17}^{+0.12}$ ). Metallicity constraints derived from ionic ratios for nine CGM systems with negligible ionization corrections and N _HI > 10 ^18.5 cm ^−2 show a significant degree of scatter (with metallicities/limits across the range $-2.06\lesssim logZ/Z_{\odot }\lesssim -0.75$ ), suggesting inhomogeneity in the metal distribution in these environments. Velocity widths of C iv λ 1548 and low-ionization metal species in the DLA versus CGM sightlines are strongly (>2 σ ) correlated, suggesting that they trace the potential well of the host halo over R _⊥ ≲ 300 kpc scales. At the same time, velocity centroids for C iv λ 1548 differ in DLA versus CGM sightlines by >100 km s ^−1 for ∼50% of velocity components, but few components have velocities that would exceed the escape velocity assuming dark matter host halos of ≥10 ^12 M _⊙ .